Metabolomics of tracheal wash samples and exhaled breath condensates in healthy horses and horses affected by equine asthma. (27th September 2018) - Bazzano, Marilena; Laghi, Luca; Zhu, Chenglin; Magi, Gian Enrico; Serri, Evelina; Spaterna, Andrea; Tesei, Beniamino; Laus, Fulvio
Abstract: The present work characterized the metabolomic profile of tracheal wash (TW) and exhaled breath condensate (EBC) in healthy horses and horses with respiratory disease. Six asthma-affected horses (group A) and six healthy controls (group H) underwent clinical, endoscopic and cytologic examinations of upper airways to confirm the active phase of asthma. TW and EBC samples were collected from each animal and investigated by proton nuclear magnetic resonance ( 1 H-NMR) metabolomic analysis. A total of ten out of 38 metabolites found in the TW were significantly different between the groups ( p < 0.05). Higher concentrations of histamine and oxidant agents, such as glutamate, valine, leucine and isoleucine, as well as lower levels of ascorbate, methylamine, dimethylamine and O-phosphocholine, were found in group A compared to group H. Eight metabolites were found in equine EBC, namely methanol, ethanol, formate, trimethylamine, acetone, acetate, lactate and butanone, previously observed also in human EBC. Despite the fact that this was a pilot study, the results showed that the metabolomic analysis of TW and EBC has the potentiality to serve as a basis for diagnostic tools in horses with asthma.